2021
DOI: 10.3390/app11209365
|View full text |Cite
|
Sign up to set email alerts
|

Salvia Species as Nutraceuticals: Focus on Antioxidant, Antidiabetic and Anti-Obesity Properties

Abstract: Salvia plants belong to the Lamiaceae family and are recognized as being strongly aromatic, being widely used for different purposes in culinary or traditional medicine. These plants are well recognized as being rich in phenolic acids, flavonoids and terpenic compounds, which exhibit health-beneficial activities, protecting against oxidative and inflammatory-related diseases, such as diabetes and obesity. Because of these properties, phytochemicals from Salvia species have been investigated as health promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 93 publications
2
9
0
1
Order By: Relevance
“…Along with other species of the mint family, the sage plants are being recognized as a promising source of polyphenols that exhibit a remarkable diversity of both chemical structures and biological activities [ 2 , 8 , 33 ]. The contents of different groups of polyphenolic components, phenolic acids, flavonoids, tannins, and anthocyanins, in the leaves of selected Salvia species, were determined spectrophotometrically and obtained results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with other species of the mint family, the sage plants are being recognized as a promising source of polyphenols that exhibit a remarkable diversity of both chemical structures and biological activities [ 2 , 8 , 33 ]. The contents of different groups of polyphenolic components, phenolic acids, flavonoids, tannins, and anthocyanins, in the leaves of selected Salvia species, were determined spectrophotometrically and obtained results are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The most abundant caffeic acid dimer identified in sage plants is rosmarinic acid, while lithospermic and salvianolic acids, sagecoumarin and yunnaneic acids are predominant among trimers derived from caffeic acid [ 5 , 6 , 7 ]. Previous research revealed the extensive biological effects of Salvia species, including antimicrobial, antioxidant, anti-inflammatory, neuroprotective, and anticancer activities, among others [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves of sages are rich in essential oils and secondary metabolites such as phenolics and terpenoids, and there is widespread knowledge and use of many native Salvia spp. in various countries for medicinal and perfumery purposes, as well as culinary plants, supported by a huge number of scientific publications [5][6][7][8][9][10][11][12]. In addition, numerous cultivars, varieties, and hybrids of Salvia are widely used worldwide as ornamental plants for their flower interest and fragrant foliage.…”
Section: Introductionmentioning
confidence: 99%
“…Clary sage (Salvia sclarea L.) belongs to the most popular species in the genus Salvia, which includes more than 900 species (Kintzios, 2000;Valant-Vetschera et al, 2003;Asadi et al, 2010;Šućur et al, 2016b;González-Chávez et al, 2017;Zengin et al, 2018;Kivrak et al, 2019;Afonso et al, 2021;Svydenko et al, 2022). Salvia sclarea is an aromatic biennial or perennial plant, 20 to 120 cm tall with a thick square stem (Angelova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%